Advanced Undergraduate Computing Students' Perception of Software Quality Teaching: a Survey in the Brazilian Paraná State - Ferrari, Guilherme N.; Nepomuceno, Thais S.; Santana, Claudia H.; Luz, Carlos D.; Leal, Gislaine C.; Amaral, Aline M. M. M.; Balancieri, Renato; OliveiraJr, Edson (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2023: Anais do XXVI Congresso Ibero-Americano em Engenharia de Software, 2023)
Aspects of software quality (SQ), such as process and product metrics, and assessment techniques, can be taught to computing students during their undergraduate courses, however, there is no consensus on how. In Brazil, computing courses are structured as the Brazilian Computer Society suggests, still, researchers point out that there are few SQ subjects in these courses. This paper aims to analyze the perception of SQ concepts by advanced undergraduate students in the northwest of the Paraná state. We applied a survey and received ninety-nine answers. Our results show that most SQ concepts are taught, but the students feel they did not learn and are not able to apply them. We discuss and suggest guidelines to improve the understanding of SQ concepts.